1992
DOI: 10.1523/jneurosci.12-10-03862.1992
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic expression of ultraviolet-rhodopsins in the blue photoreceptor cells of Drosophila: visual physiology and photochemistry of transgenic animals

Abstract: We have generated transgenic flies expressing R7 cell-specific opsins in the major class of photoreceptor cells of the Drosophila retina and characterized their spectral properties using high-resolution microspectrophotometry and sensitivity recordings. We show that the Rh3 and Rh4 opsin genes encode UV-sensitive opsins with similar spectral properties (lambda max = 345 nm and 375 nm), and that Rh3 corresponds to the R7p and R7marg class of visual pigments. We have also generated Rh3 and Rh4 isoform-specific a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
133
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 29 publications
4
133
0
Order By: Relevance
“…To discount this possibility, the profile of retinoids in flies expressing Rh4 in place of Rh1 (referred to here as pRh1:Rh4, see Ref. 35) was examined. Earlier (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To discount this possibility, the profile of retinoids in flies expressing Rh4 in place of Rh1 (referred to here as pRh1:Rh4, see Ref. 35) was examined. Earlier (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The minor rhodopsins are also bistable pigments. Misexpression of a minor opsin in the R1-6 photoreceptor cells, in the absence of Rh1, results in the production of a PDA according to the spectral characteristics of the minor rhodopsin [54,56,101]. For example, introduction of Rh2 in the R1-R6 cells results in a PDA that is produced at ∼420 nm and terminated at ∼520 nm, respectively.…”
Section: The Rhodopsin Cycle In Drosophilamentioning
confidence: 99%
“…The situation for R7y and R8y is quite different, however. R7y has a violet rhodopsin (R430-M510) and its companion R8y a green rhodopsin (R520); (Hardie 1985(Hardie , 1986Feiler et al, 1992). Like the visual pigment in the R1-6 cells, that of R7y binds 3-hydroxy-retinol and this also acts as a sensitizer here, thus boosting ultraviolet sensitivity (Hardie, 1985(Hardie, , 1986.…”
Section: Colour and Polarization Visionmentioning
confidence: 99%
“…Ectopic expression of the ultraviolet rhodopsins in the R1-6 cells combined with a thorough physiological analysis of these Stavenga amenable cells (Feiler et al, 1992) demonstrated that the Rhl gene expresses the main blue-green rhodopsin, R480, of photoreceptors R1-6; the Rh2 gene codes the violet rhodopsin, R420, of the ocelli; the Rh3 and Rh4 genes code two distinct ultraviolet rhodopsins, R345 and R375, respectively, expressed in nonoverlapping sets of R7 cells (Montell et al, 1987;Pollock and Benzer, 1988;Carulli et al, 1994). The resulting spectral sensitivities resemble those of the Musca R7p and R7y cells, respectively.…”
Section: Colour and Polarization Visionmentioning
confidence: 99%
See 1 more Smart Citation